Analysis of Innovation Product Development of The Boardgame "Kewania” - Tejoputranto, Sigit; Puspita, Niniek Fajar (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Purpose: This research aims to explore the innovation and product development process of the Kewania board game, analyze its business model, and assess its product maturity. Method: The study employs the Design Thinking framework to identify the manufacturing process, conducts a Business Model Canvas (BMC) analysis for business model examination, and utilizes the KTH Innovation Readiness Level (IRL) method for evaluating product maturity. Result: The findings indicate that "Kewania" successfully integrates design thinking, creating board games that are not only entertaining but also possess educational value. The BMC analysis identifies crucial elements in the business model, while the KTH-IRL analysis provides a comprehensive overview of the company's innovation readiness. limitation: The limitations of this research include challenges in business management, specifically positioning "Kewania" in the valley of death. Practical implications: Conclusions and recommendations encompass strategies for enhanced education, pricing, and marketing; advanced development; community collaboration; periodic evaluation; optimized distribution; innovation management; cost efficiency; customer-centric focus; strengthened branding; improved IPRL; team training; and diversified funding sources. Originality: This study contributes to the field by examining the innovation and product development of a board game in the context of design thinking, BMC analysis, and KTH IRL evaluation. Paper type: research paper.